Why Olive Produces Many More Flowers than Fruit—A Critical Analysis - Julián Cuevas (Horticulturae)
Olive (Olea europaea L.) trees produce many more flowers than fruit. In an “on” year, an adult olive tree may produce as many as 500,000 flowers, but 98% of them will drop soon after bloom as unfertilized flowers or juvenile fruit. This waste of resources that could be better invested in fruit reaching maturation requires an explanation. Several, not mutually exclusive, hypotheses explaining the possible significance of heavy flowering followed by massive and premature flower and fruit abscission are analyzed and compared based on previously published works and recent observations on olive reproductive biology. The results suggest that olive trees selectively abort fruits to enhance the quality of the seeds in the surviving fruits. Additionally, a considerable proportion of flowers appears to contribute to the male fitness of the plant by increasing pollen export. Conversely, the hypotheses attributing to resource limitation, pollination deficits, pollinator attraction, or extra flowers functioning as an ovary reserve, must be rejected for explaining the ultimate functions of massive flower production. Implications for olive orchard management are discussed.